2017
DOI: 10.1111/jopr.12654
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Obstructive Sleep Apnea in Elderly Edentulous Patients and the Possible Correlation of Serum Serotonin and Apnea‐Hypopnea Index

Abstract: OSA was found to be prevalent in edentulous subjects due to pharyngeal collapse and decreased neuromuscular control. An inverse relationship of serum serotonin levels and AHI scores was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…80 Tripathi et al conducted a study on 381 elderly patients and showed that in this group the level of serum serotonin was inversely correlated to OSA severity; therefore, the estimation of serum serotonin is a viable biomarker for diagnosing OSA. 81 Serotonin also influences other aspects of sleep and therefore, as shown in the article of Brummet et al, the 5-HTTLPR S allele was associated with worsened insomnia in patients suffering from depression, poor sleep quality, and chronic stress. 82 Even if, as Yue et al showed, the L allele of 5-HTTLPR was associated with OSA in male patients but not in female patients, Deuschle approved that the S allele of 5-HTTLPR was associated with primary insomnia in female subjects.…”
Section: Dovepressmentioning
confidence: 98%
“…80 Tripathi et al conducted a study on 381 elderly patients and showed that in this group the level of serum serotonin was inversely correlated to OSA severity; therefore, the estimation of serum serotonin is a viable biomarker for diagnosing OSA. 81 Serotonin also influences other aspects of sleep and therefore, as shown in the article of Brummet et al, the 5-HTTLPR S allele was associated with worsened insomnia in patients suffering from depression, poor sleep quality, and chronic stress. 82 Even if, as Yue et al showed, the L allele of 5-HTTLPR was associated with OSA in male patients but not in female patients, Deuschle approved that the S allele of 5-HTTLPR was associated with primary insomnia in female subjects.…”
Section: Dovepressmentioning
confidence: 98%
“…Depression, a low 5-HT state, is often associated with reduced olfactory function [54] , [55] and fluoxetine [54] , a selective serotonin reuptake inhibitor (SSRI), and venlafaxine [56] , a serotonin-norepinephrine reuptake inhibitor (SNRI), have been reported to regenerate the lost olfactory acuity in depressed patients along with the improvement in depression. Patients of obstructive sleep apnea (also a low 5-HT state) show reduced olfactory function which improves after treatment with SSRIs [57] , [58] , [59] . An interesting observation is the improvement in olfactory sensitivity during fasting [60] and, incidentally, 5-HT in fasting state is significantly increased [61] .…”
Section: Implications and Importance Of The Hypothesismentioning
confidence: 99%
“…Our results confirm the hypothesis about a change in serum serotonin levels upon elimination of intermittent hypoxia during the night in patients with OSA. Tripathi et al [45] also confirmed this hypothesis by finding an inverse correlation between the severity of OSA and the concentration of serum serotonin in elderly patients with orthodontic pathology and obesity [45].…”
Section: Discussionmentioning
confidence: 89%